Gender-moderated effects of academic self-concept on achievement, motivation, performance, and self-efficacy: A systematic review - Wang, Leihong; Yu, Zhonggen (Frontiers in Psychology, 2023)
Although academic self-concept plays a crucial role in promoting students’ education, there is a paucity of studies simultaneously exploring the gender-moderated effects of academic self-concept on several educational constructs. This study aimed to explore gender-moderated effects of academic self-concept on achievement, motivation, performance, and self-efficacy. With Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol (PRISMA-P) and STARLITE criteria, this study screened and assessed the retrieved literature, finally including 53 studies. It was concluded that academic self-concept exerted a positive influence on improving achievement, enhancing motivation, ameliorating performance, and boosting self-efficacy. It should also be noted that interrelations between academic self-concept and other educational constructs may be much more complicated than expected since gender disparities may moderate the effects of academic self-concept. Gender discrepancies in academic self-concept could account for the gap between male students and female students in subject-specific achievement, motivation, performance, and self-efficacy, especially in STEM courses. Teaching interventions and educational policies should be taken to enhance female students’ STEM courses self-concept -. Future studies should promote educational equality, highlight academic self-concept of special groups, and enhance academic self-concept in online learning.